A structural study of an arcuate thrust belt, prebetic zone, Southern Spain - Mandeville, CRM (1993)
The Prebetic Zone, the most external zone of the Betic Cordillera of southern Spain, is a thin-skinned thrust belt of Mesozoic and Tertiary rocks formed on the southern margin of Iberia and exhibits an arcuate geometry in plan view. Deformation in the Prebetic Zone was initiated during the late Burdigalian-early Seravallian and propagated NNW/NW towards the foreland in a wave of deformation which became more WNW directed with time. Formation of the dextral Socovos wrench fault and strain partitioning across it strongly influenced the development of the arc. Tectonic subsidence curves indicate a stretched continental margin in the Mesozoic. Some of these curves also show a rapid subsidence in the Miocene, represented by intramontane basins, in response to loading of thrust slices. Gravity modelling indicates a shallowing of the Moho to the east, a decrease in the depth to basement to the east and wedging of the Internal Zones beneath the Subbetic Zone. Three balanced cross-sections across the Prebetic orogen indicate a decrease in the shortening strain from 69% to 54% to 21%, with a calculated error of ±7%. Sequential 3-D reconstructions of the External Prebetics, constructed by restoring the three balanced cross-sections over four discrete time steps, show that the initial geometry of the External Prebetics was arcuate in plan view. The overall reduction of the restored area, in the horizontal plane, was 45%, with 45-53 km of dextral strike slip along the Socovos Fault. The rate of deformation varied during the Miocene; generally increasing from the Seravallian to the Messinian with a decrease in the Tortonian. The results of this study are consistent with a model of Betic-Rif evolution in which there is syn-orogenic extensional collapse of an overthickened collisional ridge in the Alboran region.